La télévision dans les démocraties. Années 30-années 1980 - Evelyne Cohen (Amnis)
Between the thirties and the eighties, television was transformed into an essential actor on the political, social and cultural scene of Western democracies. At the end of World War II, television started to be associated with the expression of the democratic ideals of society. Between 1945 and 1980, throughout several stages, the audiovisual gradually escaped State control. A new television was born.